An electrochemical quartz crystal microbalance study of adsorption processes at gold electrodes. - Ding, Tao. (University of Ottawa (Canada), 1993)
This thesis describes a study of the adsorption of anions and neutral organic molecules at gold electrodes using the electrochemical quartz crystal microbalance (EQCM). Differential capacitance, cyclic voltammetry and ring-disk methods were also used to provide further data. In perchlorate solutions (except 0.1 M HClO$\sb4)$ mass responses are flat at potentials positive of the potential of zero charge (E$\sb{\rm pzc})$ in the double layer region of potential. This seems to agree with the accepted view that perchlorate adsorbs weakly at gold. When phosphate is added to 0.1 M KClO$\sb4$ the mass response is seen to increase with increasing potential positive of the E$\sb{\rm pzc}.$ The size of this increase is proportional to the concentration of phosphate species. Differential capacitance and cyclic voltammetry data confirm the adsorption of phosphate species. Adsorption of 4,4$\sp\prime$-bipyridyl was studied because it is one of many compounds that, when adsorbed, promote the electrochemistry of cytochrome c. The presence of 4,4$\sp\prime$-bipyridyl at the electrode surface removes the mass change seen in phosphate buffer and produces a flat mass change over the potential range from $-$0.6 V to 0.6 V. Replacement of adsorbed ions is confirmed by differential capacitance experiments. When the electrode surface is oxidised in the presence of 4,4$\sp\prime$-bipyridyl, no significant mass increase is observed. The mass response also shows that reversal of the place exchange process (where an O species is inserted into the gold lattice upon oxidation) leads to removal of a small amount of adsorbate and an irreversible loss of material from the electrode. A possible mechanism has been proposed which would account for these observations. Finally, EQCM responses show clearly that adsorbed bipyridyl is easily removed from the electrode surface by washing.
Keywords: Chemistry, Analytical.